THE EFFECT OF PROJECT-BASED LEARNING ON STUDENTS’ SPEAKING SKILLS AND LANGUAGE LEARNING STRATEGIES IN THE SENIOR HIGH SCHOOL CONTEXT - Muliaty Ibrahim; Yulini Rinantanti; Vivit Rosmayanti; Nur Ina Syam (English Study Program University of Pasir Pengaraian, 2026)
This study investigates the effect of Project-Based Learning (PjBL) on senior high school students’ language learning strategies and speaking skills. While previous studies have largely focused on students’ speaking performance, this study highlights how instructional approaches can shape students’ strategic behavior during speaking activities. he research employed a quasi-experimental design with two groups consisting of 35 students each. The instruments included a language learning strategies questionnaire adapted for speaking contexts and a speaking performance test. The data were analyzed using descriptive statistics, paired-samples t-test, independent-samples t-test, and correlation analysis. The finding revealed that students in the experimental group showed a significant improvement in their use of language learning strategies compared to those in the control group (p<0.05). A strong positive correlation was also found between strategy use and speaking performance. The effect size indicated a substantial impact of Project-Based Learning. The study contributes to the existing literature by highlighting how Project-Based Learning enhances students’ strategic competence in speaking, not merely their speaking outcomes. Therefore, teachers should integrate project-based approaches to promote both strategic learning and communicative ability.